(untitled) (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2020)
The number of elderly people in today’s Brazilian society has grown over the years. However, as life expectancy increases, challenges to guarantee the rights of the elderly increase. Research reveals that institutionalization of elderly people in shelters is more and more frequent. Considering that a large part of such acts are due to family abandonment, whether material or affective, draft laws have emerged to regulate possible solutions, such as the adoption of the elderly and senexion. Thus, the present bibliographic and qualitative analysis has as its main scope to study whether Bill 105 of 2020, which institutes senexation, is in line with constitutional principles from the perspective of the rights of the elderly. The study carried out, through the deductive method, seeks to: briefly make considerations about the rights of the elderly in the Brazilian legal system; analyze Bill 105 of 2020; to present a study on the senexão institute and its differences in relation to the adoption of the elderly; expand knowledge about reverse affective abandonment, exposing its main legal consequences; and investigate constitutional principles. Finally, it was understood that, in general, Bill 105 of 2020 is in line with the principles of human dignity and social solidarity. Keywords: Elderly. Social isolation. Draft Law nº 105/2020. Reverse affective abandonment.